The Dance of Barthes. - Léger, Nathalie (CounterText, 2023)
Nathalie Léger returns to Barthes's Fragments d'un discours amoureux to highlight its continuing appeal. But can it be pinned down? Should the attempt even be made? Léger draws on a life-time of engagement with Barthes to its range of invitations in this book to think through experience and re-connect with the discourse of love. The story of these engagements begins with ones that no longer seem purposeful – the concern with classification and system; before trusting in experience again, including experiencing the manipulations of romance narratives and the search for bite-size 'truths'. Written in allusive fragments or affective propositions of its own, the piece presents Fragments d'un discours amoureux biographically, autobiographically, speculatively, pleasurably: it's an invitation to dance in a rhetorical ballet of attachments full of movement and pauses, and the distances between words and people needed to breathe the air of understanding.